Digitization of Business Administration as a Non-Formal Education Strategy in Improving the Administrative Competence of MSME Actors in Dumai City - Novelma Lastri; Dwi Hartutik; Andi Desy Musdiana; Suprasman Suprasman; Said Mustafa (Pusdikra-Publishing.com, 2025)
Digitization of business administration not only plays a role as a business operational instrument, but also as a means of non-formal education in improving the administrative competence of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of digitalization of business administration as a non-formal education strategy in developing the administrative competence of MSME actors in Dumai City. This research uses a qualitative approach with a descriptive design. Data was collected through in-depth interviews, observations, and documentation studies of MSME actors who participated in or were involved in digital-based administrative learning activities. The selection of informants is carried out purposively by considering the variety of types of businesses and the level of utilization of the digital administration system. Data analysis is carried out through the process of data reduction, data presentation, and thematic conclusion drawn. The results of the study show that the digitalization of business administration functions as an effective learning medium in increasing the understanding, skills, and independence of MSME actors in business administration management. The implementation of digital administration encourages record-keeping order, business accountability, and administrative decision-making capabilities. This research makes a conceptual contribution to the study of non-formal education management, especially in the development of digital-based administrative education models for MSME actors.